Features and management of pulmonary embolism at Chris Hani Baragwanath academic hospital - Meel, Swati (My University, 2016)
Background: Pulmonary embolism (PE) is the most common cause of preventable deaths in hospitalized patients. Objectives: To determine the incidence and associated features of PE at Chris Hani Baragwanath Academic Hospital (CHBAH) over one year. Methods: A retrospective study was performed of patients with confirmed PE on computed tomography of the pulmonary arteries (CTPA) during 2013 and by means of a formatted data collection sheet, demographical and other relevant data was collected. Results: There were 498 CTPAs requested at CHBAH in 2013 and 147 (30%) of these confirmed the presence of PE. The mean age of the patients with PE was 47 ± 15.49 years. At least 41 % of the patients with PE were HIV positive. The Wells and revised Geneva score were comparable in predicting clinical probability of PE. Only 15% of the patients with high risk PE were thrombolysed, with no documented complications. Conclusion: PE is a common and serious medical condition in CHBAH and its management needs further optimization to improve clinical outcomes.
A research report submitted to the University of the Witwatersrand, Johannesburg in fulfilment for the requirements of the degree of Master of Medicine 2016.